Correlation of predictions to get a new dental caries with residence area and parental socio-economic conditions in adolescents in Sleman DIY - Bambang Priyono; Hari Kusnanto; Al Supartinah Santoso; Dibyo Pramono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Adolescence is a period when an individual experiences physical and psychological growth, thus requiring higher energy intake. As a result, they have a high appetite, but at the same time the supervision of parents on their oral hygiene behavior is decreases. They become free to choose their preferred food, sometimes containing high carbohydrates that may increase risks of dental caries and overweight. Sleman is one of districs in Yogyakarta, also considered as an agglomeration area of Yogyakarta town, which still has urban and rural areas. Purpose: This study aimed to examine the correlation between residence area and parental socioeconomic conditions with prediction to get a new dental caries. Method: This study was an analytic survey study conducted on 275 adolescents in Sleman. Samples were selected by using stratified cluster random sampling technique. Prediction to get a new dental caries was measured by using cariogram, involving 10 variables. Residence area was observed based on territorial characteristics, such as urban and rural areas matched to their ID card. Meanwhile, parental socio-economic condition was measured on daily expenses of their parents. A multiple regression analysis with dummy variables was used to analyses the correlation between the independent and dependent variables at a confidence level of 95%. Result: The results showed that the prevalence of caries in those adolescents in urban areas was 70.7%, while 81.95% in rural areas. The DMFT index in urban areas was 2.27, while 2.65 in rural areas. The mean percentage of prediction to get a new dental caries in urban areas was 47.83 ± 23.63, while 53.61 ± 24.68 in rural areas. The results of the statistical analysis then showed that there was no significant correlation of residence area and parental sosio-econimic conditions with prediction to get a new dental caries. Conclusion: In conclusion, residence areas, rural and urban areas, and parental socio-economic conditions, from low to high economic status were not correlated with prediction to get a new dental caries in adolescents.